Rotational Slip Flow in Coaxial Cylinders by the Finite-Difference Lattice Boltzmann Methods (Communications in Computational Physics, 2020)
Recent studies on applications of the lattice Boltzmann method (LBM) andthe finite-difference lattice Boltzmann method (FDLBM) to velocity slip simulationsare mostly on one-dimensional (1D) problems such as a shear flow between parallelplates. Applications to a 2D problem may raise new issues. The author performednumerical simulations of rotational slip flow in coaxial cylinders as an example of 2Dproblem. Two types of 2D models were used. The first were multi-speed FDLBM modelsproposed by the author. The second was a standard LBM, the D2Q9 model. Thesimulations were performed applying a finite difference scheme to both the models.The study had two objectives. The first was to investigate the accuracies of LBM andFDLBM on applications to rotational slip flow. The second was to obtain an experienceon application of the cylindrical coordinate system. The FDLBM model with 8directions and the D2Q9 model showed an anisotropic flow pattern when the relaxationtime constant or the Knudsen number was large. The FDLBM model with 24directions showed accurate results even at large Knudsen numbers.